Polymer Coating Embolism: Cause of Left Pulmonary Artery Stenosis in an Infant - Amane Matsuura; Yo Kajiyama; Tomoko Iehara (Annals of Internal Medicine: Clinical Cases)
Hydrophilic polymer coatings were designed to reduce friction between a catheter and vessel wall and facilitate inserting catheters in small vessels. In recent decades, catheter interventions have been increasingly diagnosed as a possible cause of hydrophilic polymer emboli in adults. However, there is little clinical evidence in pediatric patients. This study documents an infant with severe left pulmonary artery stenosis with calcification caused by hydrophilic polymer emboli, as confirmed by pathologic analysis. Procedures for catheter insertion and retrieval in peripherally central venous were the plausible cause. This study aims to draw pediatricians’ attention to the risk of hydrophilic polymer emboli.